Using Educational Games for Sign Language Learning - A SignWriting Learning Game: Case Study - Bouzid, Yosra; Khenissi, Mohamed Ali; Essalmi, Fathi; Jemni, Mohamed (Journal of Educational Technology & Society, 2016)
ABSTRACT Apart from being used as a means of entertainment, computer games have been adopted for a long time as a valuable tool for learning. Computer games can offer many learning benefits to students since they can consume their attention and increase their motivation and engagement which can then lead to stimulate learning. However, most of the research to date on educational computer games, in particular learning versions of existing computer games, focused only on learner with typical development. Rather less is known about designing educational games for learners with special needs. The current research presents the results of a pilot study. The principal aim of this pilot study is to examine the interest of learners with hearing impairments in using an educational game for learning the sign language notation system SignWriting. The results found indicated that, overall, the application is useful, enjoyable and easy to use: the game can stimulate the students' interest in learning such notations.
Keywords: ⛔ No DOI found

Framework for Teacher Support During Remote Teaching in a Crisis: COVID-19, as a Case Study - Denden, Mouna; Tlili, Ahmed; Burgos, Daniel; Jemni, Mohamed; Huang, Ronghuai; Essalmi, Fathi; Chang, Ting-Wen (Radical Solutions for Education in a Crisis Context, 2021)